AMPHIBIAN DISTRIBUTION ON DEGRADATED HABITAT IN PASIR BINTANG AND MANDURIANG DISTRICT GUNUNG RAYA WILDLIFE SANCTUARY AREA OF SOUTH SUMATRA PROVINCE - Aditya Yulistio; Zulkifli Dahlan; Zazili Hanafiah (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Amphibian distribution on degradated habitat in Pasir Bintang and Manduriang districts of the Gunung Raya Wildlife Reserve, South Sumatra Province is caused by human activities, namely illegal logging and coffee plantations. Amphibians are one of the components that make up ecosystems that are very sensitive to environmental changes. This study aims to know the pattern of the amphibian species distribution on degradated habitat as a first step in conserving them. The method used is a line transect combination method with an encounter survey or Visual Encounter Survey (VES) with a time search of 3 hours in both aquatic and terrestrial habitats and the coordinates of the encounter are recorded. Trap by using a drift fence and pitfall traps at the affected location and also by using the interview method with the surrounding community and forest police. Determination of the distribution of amphibians is done by mapping the coordinates of the encounters that have been recorded using GPS with the help of the location of the coordinates on Google Earth into the amphibian distribution map. The results obtained are in the form of mapping the coordinates of amphibian encounters in the affected area. The conclusion of this study is the distribution of amphibian species in degradated habitat that have been encroached by illegal logging and coffee plantations are very few types and limited distribution due to habitat destruction and the small amount of food available.